A case of infantile strongyloidiasis associated with Salmonella infection: diagnostic considerations - V.V. Mavrutenkov; A.V. Cherginets; O.V. Shvaratska; L.M. Cherginets (Zaslavsky O.Yu., 2019)
Background. Pediatric co-infections are an emerging clinical problem due to their increasing prevalence and tendency to transform a typical clinical presentation of particular diseases. Thereafter, it tangles the accurate estimation of etiology, complicates the management and negatively impacts the outcome. Given the climatic changes, significant migratory flows and international tourism, tropical helminthiases, previously not common in Ukraine, are a real threat to the public health, especially in combination with other pathogens. Materials and methods. We observed a case of strongyloidiasis and salmonellosis in a Ukrainian 5-month-old female infant who had no history of visiting any of the sub- or tropical territory of the globe. The girl came from a socially vulnerable family and was abandoned by her homeless parents immediately after admission. The girl presented with severe toxic manifestations, diarrhea, developmental delay, moderate-to-severe malnutrition and dehydration, and maculopapular rash on the trunk and lower extremities. Direct light microscopy of feces revealed Str. stercoralis in the number of more than 10 mobile larvae per high-power field, at different stages of development. Bronchial lavage fluid contained no larvae of Str. stercoralis. Fecal culture revealed group D S. enteritidis. Chemotherapy with ceftriaxone IV and oral albendazole resulted in elimination of both pathogens. Conclusions. The given case of S. enteritidis and Str. stercoralis co-infection should be considered as a probable case of autochthonous Str. stercoralis infection, as it was not confirmed by more reliable diagnostic methods (e.g. PCR for Str. stercoralis DNA), and demonstrates a doubtful epidemiological history. Consequently, to improve the diagnosis of endemic parasitic infections, it is necessary to introduce such a verification as compulsory, and mandatory registration of relevant cases in the Ukrainian National System of Epidemiological Surveillance and Biosecurity is required.